Efek Pupuk Organik Air Kelapa pada Pertumbuhan dan Hasil Selada di Bigaro Halmahera Timur - Samad, Sofyan; A. Mahmud, Shubzan (Journal of Comprehensive Science, 2025)
Lettuce plant (Lactuca sativa L) vegetable of the world community. The purpose of coconut water organic fertilizer as a nutrient for the growth and yield of lettuce plants. Method. This research was conducted from March to July 2022 in the farmer garden of Nusajaya East Halmahera, North Maluku. Lettuce seed plant material, Coconut water organic fertilizer and with the following treatments: B1 treatment without coconut water organic fertilizer 0 cc / 1 liter of water / 3 polybags, B2 treatment of coconut water organic fertilizer at a dose of 10 cc / 1 liter of water / 3 polybags B3 treatment of coconut water organic fertilizer at a dose of 15 cc/1 liter of water/3 polybags, B4 treatment of coconut water organic fertilizer at a dose of 20 cc/1 liter of water/3 polybags. B5 treatment of coconut water organic fertilizer with a dose of 25 cc/1 liter of water/3 polybags. Agronomic parameters include: 1) Lettuce height (cm), 2) many lettuce leaves, 3) Length (cm), 4) Leaf width, 5) Fresh weight of the sample (g) with variety analysis (Anova). The results showed that coconut water 20 cc/L water/3 polybags (P5) had an effect on all observation variables of lettuce, at the age of 10 HST was 13 cm high, at the age of 20 HST the highest was 18 cm and at the age of 30 HST was 24 cm high. Meanwhile, when harvesting, it produced a total of 16 leaves, the longest leaf was 20 cm, and the heaviest sample weight was 130 g when compared to other treatments. Macro and micro particles in coconut water can accelerate the increase in the size and length of lettuce. So that the content of macro (such as potassium) and micro elements (such as magnesium) in coconut water is proven to accelerate growth and increase the yield of lettuce plants.